2007
DOI: 10.1021/jo070018t
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Strategies Mediated by Lanthanide Triflates for Efficient Assembly of Oligomannans

Abstract: Readily prepared mannosyl n-pentenylorthoesters (NPOEs) serve as donors in themselves and as convenient intermediates for other glycosyl donors, such as n-pentenyl glycosides (NPGs), thioglycosides, and trichloroacetimidates. These various donors are activated by different reagents, and are therefore amenable to versatile, discriminate use. Scandium and ytterbium triflates respond very differently to these donors, with the result that chemoselective discrimination between NPOEs, NPGs, trichloroacetimidates as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
(31 reference statements)
0
24
0
1
Order By: Relevance
“…[5] The versatility of NPOE donors was further demonstrated recently in the efficient assembly of a pentadecamannan. [121] In this synthesis, NPOEs served not only as donors, but also as convenient intermediates in the generation of other glycosyl donors, such as trichloroacetimidates, thioglycosides, and NPGs. Propargyl 1,2-orthoesters, such as 51, have also been reported recently as glycosyl donors (Scheme 7 d).…”
Section: 2-orthoesters Of Aldosesmentioning
confidence: 99%
“…[5] The versatility of NPOE donors was further demonstrated recently in the efficient assembly of a pentadecamannan. [121] In this synthesis, NPOEs served not only as donors, but also as convenient intermediates in the generation of other glycosyl donors, such as trichloroacetimidates, thioglycosides, and NPGs. Propargyl 1,2-orthoesters, such as 51, have also been reported recently as glycosyl donors (Scheme 7 d).…”
Section: 2-orthoesters Of Aldosesmentioning
confidence: 99%
“…Die Vielseitigkeit der NPOE‐Donoren wurde vor kurzem bei der effizienten Herstellung eines Pentadecamannans erneut belegt,121 indem NPOEs nicht nur als Donoren fungierten, sondern auch als geeignete Intermediate für andere Glycosyldonoren, z. B. Trichloracetimidate, Thioglycoside und NPGs.…”
Section: Glycosyldonoren Und Aktivierungsbedingungenunclassified
“…Besides, the complexity of the system further complicates attempts of rationalization. Fraser-Reid et al, who have addressed more systematically the regioselective glycosylation of diol systems, [31][32][33][34][35][36] has suggested that primary hydroxyl groups can only be considered more reactive than secondary hydroxyl groups in reaction with disarmed glycosyl donors and orthoesters and that armed glycosyl donors can favour glycosylation at the secondary rather than the primary position. 33 Our present data do not permit any interpretation of the obtained results on the basis of this suggestion.…”
Section: Resultsmentioning
confidence: 99%